Morpho-agronomic characteristics of the interspecific hybrid Cucurbita ficifolia x C. maxima - Ivančič, Anton (Agricultura (Maribor), 2004)
The aim of the investigation was to describe some of the main morpho-agronomiccharacteristics of the interspecific hybrid Cucurbita ficifolia x C. maxima, and to define the traits which can be used for distinguishing this hybrid from the parental species. The hybrid was obtained using emryo-rescue technique. The plants were extremely vigorous and were growing and flowering until the first frost. The ratio male versus was rangingbetween 1:40 and 1:80. Most of the male and female were sterile or partly sterile. The majority of the analysed traits were intermediate regarding the parental species. The most appropriate traits for the determination of the interspecific nature were the leaf margin, the shape and colour of ripe fruits and the shape of fruit stalks. The fruit exterior was extremely hard (similarly to the one of C. ficifolia) and cracked in several places.
Keywords: agriculture; kmetijstvo; buče; Cucurbita ficifolia; Cucurbita maxima; hibridizacija; morfologija